Arabic Public Speaking in Malaysia: Enhancing Vocabulary and Confidence through Psycholinguistics - Solehudin, Muhamad; Nur Hanifansyah (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
This study explores the impact of Arabic oratory on vocabulary acquisition and public speaking confidence among students in Malaysia, where Arabic is mainly learned for religious purposes. The research aims to assess the effectiveness of Arabic Public Speaking (khitabah) in enhancing language retention and building self-assurance in public speaking through a psycholinguistic approach. Using a mixed-methods design, data were collected from 30 Form Four students at Maktab Mahmud Yan through qualitative interviews, classroom observations, and quantitative pre- and post-tests. The findings show a 20% improvement in vocabulary mastery and a 50% increase in public speaking confidence following weekly oratory sessions. Psycholinguistic strategies, such as voice projection and positive reinforcement, were instrumental in reducing student anxiety. The study introduces a novel integration of Arabic oratory with psycholinguistic techniques, demonstrating a dual impact on language proficiency and confidence. This research suggests that embedding Arabic oratory in language curricula can significantly improve both vocabulary acquisition and speaking skills, offering a holistic method for language development in similar educational contexts.